An Efficient Technique to Detect Stegosploit Generated Images on Windows and Linux Subsystem on Windows - N, Vaidya; P, Rughani (International Journal of Computer Sciences and Engineering, 2019)
Steganography as being a very useful technique for content hiding is the first choice of criminals, terrorists, and hackers. The steganalysis itself is very complex, and lots of research work is going on all around the world on steganography and steganalysis. However, when the steganography hides exploit instead of simple messages, it becomes more severe and damaging. Stegosploit is a similar toolkit that allows hackers to inject exploits for known vulnerabilities into images. These images, when accessed or downloaded can infect a machine very effectively compared to other ways of doing it. This paper emphasis on a technique that detects such stego images having an exploit inside it. We developed a script that detects this type of image, which is in-general not identified by known anti-viruses including virus total. The study also focuses on the effectiveness of the script for the Windows operating system and Linux Subsystem on Windows. The script derived from this research will help end-users, security professionals, forensic investigators, and researchers in detecting and thus preventing possible cybercrimes.